Reduced Effect of Commercial Leonardite and Seaweed Extract on Lettuce Growth under Mineral, Organic, and No Fertilization Regimes - Peltier Aguiar; Gediane Maria Garcia Corrêa; Manuel Ângelo Rodrigues; Margarida Arrobas (Agronomy, 2024)
In this study, two commercial products based on the main groups of contemporary biostimulants—a commercial leonardite and a seaweed extract—were tested with the objective of assessing the conditions under which they can enhance lettuce (Lactuca sativa L.) performance, particularly to determine if synergies with conventional fertilization methods can be observed. The experimental protocol was arranged as a factorial design with two factors: organic or mineral fertilization × plant biostimulant. The organic or mineral fertilization factor included five levels: two rates of a nitrogen (N) fertilizer (40 (Nmin40) and 80 (Nmin80) kg ha−1 of N), the same N rates applied as an organic amendment (Norg40 and Norg80), and an unfertilized control (N0). The plant biostimulants used were a commercial leonardite (leonardite) for soil application before planting, a commercial seaweed extract (algae) for foliar application during the growing season, and a control without plant biostimulant. Leonardite significantly increased lettuce dry matter yield (DMY) compared to the control only in the first growing cycle (11.5 and 13.5 g plant−1) and showed no significant interaction with conventional fertilization. It also consistently increased phosphorus (P) levels in the plant tissues. The seaweed extract did not show any effect on the plant, nor did it have any interactions with conventional fertilization regarding DMY. In contrast, with mineral fertilization, lettuce DMY increased from 8.0 and 4.0 g plant−1 (N0) to 22.2 and 12.0 g plant−1 (Nmin80) in the first and second growing cycles, respectively. The response to organic fertilization was lower, yet DMY still increased from 4.0 to 8.1 g plant−1 in the second growing cycle. Generally, this type of plant biostimulant is tested under some form of environmental stress, where it often yields positive results. In this study, the optimal cultivation conditions maintained for the lettuce in the pots likely explain the limited response to the biostimulants. This study suggests that the product labels should more clearly indicate whether they are recommended for general cultivation conditions or specifically for situations where a particular environmental stress can be anticipated.